IMPLEMENTASI KEBIJAKAN PENDAFTARAN TANAH SISTEMATIS LENGKAP BERBASIS PARTISIPASI MASYARAKAT DI KABUPATEN BALANGAN - Didik Prasetyo Widiyanto; Muslih Amberi (Jurnal PubBis, 2023)
This study aims to examine the implementation of a complete systematic land registration policy based on community participation (PTSL-PM) in Balangan District, South Kalimantan Province. The research method used is a qualitative research method with a descriptive approach, while data collection techniques are through interviews, observation and documentation. The analysis technique used is the model from Mazmanian and Sabatier. Meanwhile, the extent to which the Balangan district community is involved in supporting PTSL-PM activities is analyzed using Arnstein's concept of the eight steps of community participation. The results of the study show that the influential variables according to this theory have indirectly been identified, analyzed and searched for a solution strategy in its implementation so that PTSL-PM activities in Balangan district can meet the number of predetermined physical and financial completion targets. In addition, the involvement and participation of the Balangan Regency community members which is one of the advantages of PTSL-PM activities in Balangan Regency is in degrees of tokenism and is included in the fifth Placation ladder. In this position the expected form of community participation still requires intensive assistance from the Balangan District Land Office Team. Keywords: Policy Implementation, Community Participation, Land Registration, PTSL-PM